Analysis of The Most Dominant Dental Carries Risk Factors on High def-t and DMF-T Value of Students Age 6-12 Years - ardiwirastuti, ilvana; Gusbela , Balqis Istiqomah; Santoso, Olivia Maulana; Tias, Richa Rochmani Adining; Siahaana, Sahat Manampin (Poltekkes Kemenkes Yogyakarta, 2024)
Background: Riset Kesehatan Dasar (Riskesdas) shows that the highest rate of dental caries in children occurs in the 5–9 y.o group (92.6%). Dental caries should be prevented early by reducing the factors that cause caries. The def-t/DMF-t caries index can be used to assess the severity of dental caries, while the caries risk assessment can be used to study the various variables that cause dental caries. Objectives: To analyze the most dominant risk factors for dental caries with the highest def-T/DMF-T values in students in grades 1-6 at SDN Cenlecen 1 Pakong Pamekasan. Methods: This study is analytical and observational with a Cross-sectional method approach. The data analysis used the Chi-square test to examine the relationship between the variables. Results: This study shows that the most significant correlation value for high deft-t/DMF-T is eating and drinking sweet foods (p-value, 0.027), followed by having a mother who had dental caries experience, receiving dental care, having teeth lost as a result of caries, having visible plaque, and exposed root surfaces. Conclusion: The most dominant risk factor for dental caries for high def-T/DMF-T rates at SDN Cenlecen 1 Pakong Pamekasan is eating and drinking sweet foods.